Quelle visibilité chrétienne dans la ville contemporaine ? - Olivier Chatelan (Territoire en Mouvement)
The creation of a central business district in the Part-Dieu’s area in Lyon at the beginning of the 1970’ leads the Archbishop’s palace to send on-site a priest of the diocese, Jean Latreille, in order to envisage an adequacy Church’s place to an original town planning. This chaplain of the Lyon’ students had studied philosophy. He would like to understand what is at stake in the urban modernity and he gathers a sound material to that purpose. He gets in touch with several persons – include outside of the Church – to realize the specificities of this regional equipment. Several solutions are planned, which are the expression of differentiated experiences of the modern city for the Catholics. Is it necessary to build again a place of worship, such as the Diocese has built many during about fifteen years to adapt the parish meshing to the growth of population in Lyon and its suburbs ? Should be a silent place for contemplation enough in this space with so much unceasing mobility ? The ecumenical center “Mains ouvertes” with difficulty opens in 1975. The discussions about it are telltale of a moment of the French Catholicism’ history, when the visibility and the diocesan strategies embarrass militant organizations which want another way to take part in the town planning.